Nutritional epidemiology - Willett, Walter (Oxford : Oxford University Press, 2013)
This title is about the complex relationships between diet and risks of important diseases, such as cancer and cardiovascular disease. It features an overview of research strategies in nutritional epidemiology - still a relatively new discipline that combines the vast knowledge compiled by nutritionists during this century with the methodologies developed by epidemiologists to study the determinants of diseases with multiple etiologies and long latent periods. A major section is devoted to the methods of dietary assessment using data on food intake, biochemical indicators of diet, and measures of body composition and size. The reproducibility and validity of each approach and the implications of measurement error are considered in detail.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Nutritionally induced diseases -- Epidemiology; Diet in disease -- Research -- Methodology; Nutrition surveys -- Methodology; Nutrition -- Research -- Methodology